PEMODELAN KEPUASAN NASABAH KREDIT UMUM MENGGUNAKAN PELAYANAN DAN DAYA TARIK PRODUK - Suharto Suharto (Universitas Muhammadiyah Metro Lampung, 2016)
ABSTRACT The method used in this research is explanatory survey method. This type of research is quantitative research with the object of research is a service, product appeal and customer satisfaction. The study population of customers at Bank Eka Bumi Arta Metro City with a total sample of 80 customers were taken using accidental sampling technique. Decision-making research results based on the results of the analysis using multiple linear regression analysis. The purpose of this study was to analyze the influence of services and product appeal to customer satisfaction of public credit at Bank Eka Bumi Artha Metro City. Type of research is descriptive qualitative research procedures that produce descriptive data based on the results of a quantitative analysis of the variables of the study. The technique of collecting data using interviews, documentation and questionnaires using a questionnaire. The analysis tool used is to use data quality analysis and multiple linear regression analysis. In conclusion, the resulted of analytical services have a significant impact on customer satisfaction. The appeal of the products have a significant impact on customer satisfaction. Fascination services and products simultaneously have a significant influence on customer satisfaction. These results it can be summary that the independent variables are positive and significant impact on customer satisfaction. Keywords: Services, Fascination Products, Customer Satisfaction.